Epigenetics: general characteristics and implications for oral health - Ji-Yun Seo; Yoon-Jung Park; Young-Ah Yi; Ji-Yun Hwang; In-Bog Lee; Byeong-Hoon Cho; Ho-Hyun Son; Deog-Gyu Seo (Korean Academy of Conservative Dentistry, 2015)
Genetic information such as DNA sequences has been limited to fully explain mechanisms of gene regulation and disease process. Epigenetic mechanisms, which include DNA methylation, histone modification and non-coding RNAs, can regulate gene expression and affect progression of disease. Although studies focused on epigenetics are being actively investigated in the field of medicine and biology, epigenetics in dental research is at the early stages. However, studies on epigenetics in dentistry deserve attention because epigenetic mechanisms play important roles in gene expression during tooth development and may affect oral diseases. In addition, understanding of epigenetic alteration is important for developing new therapeutic methods. This review article aims to outline the general features of epigenetic mechanisms and describe its future implications in the field of dentistry.